The Effect of Traffic Volume on Remaining Service Life Based on Empirical Mechanistic Method - Dahlia Dahlia; Arief Setiawan; Novita Pradani (PT Publikasiku Academic Solution, 2025)
Hangtua Road in Palu City serves as a vital connector between the Talise and Tondo sub-districts, providing access to educational institutions, commercial areas, and residential zones. The road segment has shown visible structural damage at several points, raising concerns about its serviceability under increasing traffic demand. The problem addressed in this study is the decline in pavement performance, which threatens road safety and accessibility. The objective is to evaluate the stress and strain levels of the pavement, estimate its remaining service life, and propose appropriate maintenance solutions. A descriptive research method was employed, supported by field investigations. Primary data were collected from the Benkelman Beam (BB) deflection test and the Dynamic Cone Penetrometer (DCP) test for CBR values. The maximum deflection recorded was 0.325 mm at STA 0+500, while the minimum was 0.168 mm at STA 0+700. The analysis indicates that the existing pavement structure can continue to serve adequately if supported by routine maintenance. The recommended solution is the application of a non-structural overlay, which is expected to extend the pavement's service life by approximately 10 years while accommodating projected traffic growth. These findings provide practical guidance for local road authorities in planning cost-effective and sustainable maintenance strategies.